Brand and Political Campaign Tools Development for Anis Matta ( Justice and Prosperous Party President) Using Design Thingking Approach - Arifin, Akhmad Mukhamad; Larso, Dwi (The Indonesian Journal of Business Administration, 2014)
Abstract. Anis Matta was one of five candidates nominated as the President of the Republic of Indonesia by the Prosperous Justice Party (PKS) for Indonesian presidential election in July 2014. Anis Matta electability rate stood at 3.42% based on survey results from INSTRAT in November 2013, far from the strongest candidate Joko Widodo 28.9%. Mawar Melati Creative Strategic as creative consultants were asked to generate creative solutions to improve Anis Matta electability for the presidential election. The final project will use Design Thinking approach, consists of Define-Observe-Reframe-Ideate-Prototype-Implement-Evaluate phases. The end result of this study is the brand AMPM: Anis Matta Pemimpin Muda and some visual campaign products such as brochures, stickers etc. These campaign tools has been implemented nationally by Gen AMPM and PKS on Legislative Elections campaign period from February to April 2014. Anis Mattaâ€™s electability increased to 14,6% measured by survey in end of March 2014.Keywords: political marketing, design thinking, Anis Matta, PKS, political brand, Indonesian presidential election in 2014Â